Therapeutic and post-lesional aspects of enzootic pneumonia in pigs - Adrian C. Stancu (Medicamentul Veterinar, 2013)
The mycoplasmas are causing significant economic damage, these conditions being constant attention of farmers and veterinary services. Economic losses may be due to mortality, veterinary restrictions, a decrease in meat production, increased feed consumption and expenditure specific therapeutic and control measures. The conducted reaserches aimed at methods of disease treatment and diagnosis of enzootic pneumonia based on morphopathological lesions (macroscopic and histopathological)in dead pigs cases.